Endoscopic surgery in the treatment of crista galli pneumatization evolving with localizated frontal headaches - Socher, Jan Alessandro; Santos, Pedro Geisel; Correa, Vinicius Cidral; Silva, Leandro Caetano de Barros e (International Archives of Otorhinolaryngology, 2013)
Introduction: The crista galli is part of the ethmoid bone and thus may suffer from the process of pneumatization. Pneumatization occurs in between 3% and 14% of patients, resulting from air cells in the frontal or ethmoid sinuses.Aim: To describe 3 cases of crista galli pneumatization in which the patients developed infection and were treated surgically by endoscopic techniques.Method: We present 3 case studies of patients complaining of severe frontal headaches. The patients underwent ENT evaluation, examination by video-endoscopy, and computed tomography, which identified crista galli pneumatization with mucosal thickening and the presence of fluid. Patients underwent treatment with antibiotics and corticosteroids; however, they showed no symptomatic improvement, displayed recurrence of symptoms, and maintained radiographic changes. Thus, patients then underwent drainage through the crista galli via an endoscopic procedure.Discussion: During surgery, mucopurulence and/or mucosal thickening and edema were identified in the pneumatized crista galli. There were no complications during or after surgery. Postoperatively, headache was improved in patients after a minimum follow-up of 6 months.Conclusion: Crista galli pneumatization can result in infection, simulating rhinosinusitis. When there is little response to drug therapy, endoscopic surgical treatment is required; the current cases demonstrate that this technique is safe and effective.
Keywords: Natural Orifice Endoscopic Surgery; Video-Assisted Surgery; Headache